DOES MRS-GARCH OUTPERFORMS THE SINGLE GARCH-TYPE MODELS FOR FORECASTING? - Pereira Conte, Bruno; Universidade Federal de Santa Maria (2019)
This paper evaluated if the Markov switching regime GARCH models can outperforms the single GARCH-type models on forecasting. To achieve this objective, it was used the Brazilian stock market – Ibovespa –  between 2012 and 2017 as study scope. The major difference of our work is the definition of the in-sample and out-of-sample pattern. This paper determined a 200 steps-ahead (10 months) forecast, with model re-estimation at each step-ahead, in order to find conclusive evidence and robust results of the model which has better predictive ability. The results showed that the single GARCH-type models show a slightly better performance for VaR at 5% and switching regime models had better performance at 1% and predictive accuracy considering the most of statistical criteria. Besides that, no model could be determined as benchmark by statistical criteria, which displays that there´s no way to determine a model that outperforms for forecasting on the Brazilian stock market.